Obstacles to freedom of expression in sports media in Algeria from the point of view of media professors at the University of M'sila - جلال, صلاح الدين (sports creativity, 2025)
he article deals with freedom of expression in sports media in Algeria from the point of view of media professors at the University of M'sila. The importance of the study lies in the quality of the study population and sample, who are specialists in the media, which gives its results greater accuracy and impartiality. The study included 30 professors who were distributed a questionnaire that enabled three axes and After the quantitative and qualitative analysis, the study concluded that there are positive trends towards freedom of expression in the Algerian sports media among media professors at the University of M'sila, despite the presence of some negative trends, which are due to the deep vision of the requirements of freedom of expression among the respondents being professors in the media. The study may be an introduction to the legislator from In order to remedy some of the legislative deficits in order to consolidate the gains of freedom of speech in the sports media.